Relationship of Knowledge with Breastfeeding Mother's Attitude About Oxytosin Massage On The Smoothness Ofreast Milk Elisabet Purba New Midwife Clinic South Panyabungan District Year 2021 - Helmi wardah Nasution (Science Midwifery, 2021)
Oxytoxin massage is done to stimulate the oxytocin reflex or let me down reflex. Exclusive breastfeeding in Indonesia is still far from expectations. Nationally, the coverage of infants receiving exclusive breastfeeding in 2017 was 61.33%. However, this figure has not reached the target of exclusive breastfeeding coverage set by the government, which is 80%. The design of this research is analytic with cross sectional study approach. This type of research is descriptive correlational. The population in this study were all postpartum mothers at the Elisabeth Purba Baru Midwife Clinic. The sampling technique was a total sampling technique of 35 people.The results of the study, analysis of the chi-square test, obtained by the analysis of the Chi-Square test, it is known that the significant value of p value is 0.035. (0.035 <0.05) then Ho is rejected and Ha is accepted so that in this study there is a significant relationship between knowledge and attitudes of breastfeeding mothers about oxytocin massage on breastfeeding smoothness at the Elisabeth Purba Baru Midwife Clinic. It is hoped that research sites, institutions, respondents and further researchers are advised to apply oxytocin massage to nursing mothers and explain the benefits to mothers so that mothers' knowledge increases and their attitudes are positive towards oxytocin massage